O Espírito e a esposa dizem: vem! - a figura da esposa como resposta profética à unidade da Igreja - Pazeto, Mayara Amaral (2023)
The Wife in scripture is not limited to a specific character, but progressively reveals herself to be necessary for the biblical plot. Hidden in many faces, she proves essential for the development of the love narrative built in the dialogue between God and His people. She is a symbol of the Covenant and an image of divine knowledge: the marital bond is presented in scripture as the relationship between God and Israel, absorbed by Christ and the Church. Within the building of this loving relationship and bond, it is the Spirit that is present, shaping the Wife into a prophetic response, as she becomes one body, one flesh: the great mystery of unity